Development, validity, and normative data study for the 12-word Philadelphia Verbal Learning Test [czP(r)VLT-12] among older and very old Czech adults - Bezdicek, Ondrej; Libon, David J; Stepankova, Hana; Panenkova, Erika; Lukavsky, Jiri; Garrett, Kelly Davis; Lamar, Melissa; Price, Catherine C; Kopecek, Miloslav (The Clinical neuropsychologist, 2014)
The aim of the present study was to assess the validity of a 12-word Czech version of the Philadelphia (repeatable) Verbal Learning Test [czP(r)VLT-12]. The construction of the czP(r)VLT-12 was modeled after the California Verbal Learning Test (CVLT) and the nine-word Philadelphia (repeatable) Verbal Learning Test [P(r)VLT]. The czP(r)VLT-12 was constructed from a large corpus of old (60-74) and very old (75-96) Czech adults (n = 540). Participants met strict inclusion criteria for the absence of any active or past neurodegenerative disorders and performed within normal limits on other neuropsychological measures. Principal component analysis (PCA) and correlations between czP(r)VLT-12 factor structure and other memory tests were conducted. The czP(r)VLT-12 produced a four-factor solution, accounting for 70.90% of variance, with factors related to: (1) recall, (2) extra-list intrusion errors/recognition foils, (3) interference, and (4) acquisition rate; a solution similar to the CVLT and P(r)VLT. Increasing age resulted in a decline in most czP(r)VLT-12 indices, women outperformed men, and higher education led to higher scores. Memory performance in normal aging did not correlate with instrumental activities of daily living. Low, but significant, correlations were seen with other tests of cognitive performance (divergent validity). Appendices are available that provide normed percentile estimates of individual czP(r)VLT-12 performance stratified by age, education, and gender. In accordance with previous studies, these results demonstrate the usefulness of czP(r)VLT-12 in assessing declarative memory in older adults.
Keywords: Middle Aged; Normative data; verbální učení; Neuropsychological Tests; Philadelphia (Repeatable) Verbal Learning Test; Memory; lidé středního věku; paměť; Mental Recall; mužské pohlaví; Aged, 80 and over; rozpomínání; vzorkové studie; Humans; senioři; The Boston Process Approach.; lidé; Aging; Declarative memory; Czech Republic; Sampling Studies; Female; senioři nad 80 let; Česká republika; Verbal Learning; Aged; ženské pohlaví; stárnutí; neuropsychologické testy; Male; P(r)VLT; Normal aging